2014
DOI: 10.7306/gq.1189
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of the Carpathian thrust front between Tarnów and Pilzno (Pogórska Wola area, southern Poland) – results of integrated analysis of seismic and borehole data

Abstract: Seis mic data and core from the shal low car to graphic Pilzno P-7 bore hole were used to con struct a new model of the Carpathian orogenic front be tween Tarnów and Pilzno, in the Pogórska Wola area (south ern Po land). The most ex ter nal, fron tal thrust of the orogenic wedge (the Jaoeniny struc ture) was iden ti fied as a syn-depositional fault-prop a ga tion fold detached above the Up per Badenian evaporites. Its for ma tion was con trolled by the pres ence of me chan i cally weak foredeep evaporites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 42 publications
(58 reference statements)
1
19
0
1
Order By: Relevance
“…(Summary after ten Haven et al, 1993;Lafargue et al, 1994;Kotarba and Koltun, 2006;Matyasik and Dziadzio, 2006;Oszczypko et al, 2006;Pawlewicz, 2006;Slaczka et al, 2006;Krobicki et al, 2012;Kotarba et al, 2013;Slaczka et al, 2014;Krzywiec et al, 2014;Machowski et al, 2017;Waskowska et al,2018;Kosakowski et al,2018 this issue)…”
Section: North Carp Pa Pa P Thian Fold-thrust Province Thian Fold-thrunclassified
“…(Summary after ten Haven et al, 1993;Lafargue et al, 1994;Kotarba and Koltun, 2006;Matyasik and Dziadzio, 2006;Oszczypko et al, 2006;Pawlewicz, 2006;Slaczka et al, 2006;Krobicki et al, 2012;Kotarba et al, 2013;Slaczka et al, 2014;Krzywiec et al, 2014;Machowski et al, 2017;Waskowska et al,2018;Kosakowski et al,2018 this issue)…”
Section: North Carp Pa Pa P Thian Fold-thrust Province Thian Fold-thrunclassified
“…Thrusting was accompanied by the formation of the Carpathian foredeep basin [ Oszczypko , ]. In the sector of the Outer Carpathian belt located to the north of the Tatry, the main thrusting phase ceased after ~13.6 Ma [ Nemčok et al ., , ] and the final stages of tectonic activity within the frontal orogenic wedge took place after ~12 Ma [ Krzywiec et al ., ].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…In the southern segment of the seismic time section ( fig. 10 in Krzywiec et al 2014) -with the course similar to that of the cross section from our Fig. 6A -the quoted authors plotted (with a question mark) a backthrust that suggested a tectonic character of the unconformable position of the Miocene sediments on the Skole Nappe.…”
Section: Specific Features Of the Tectonics Of The Miocene Molassementioning
confidence: 60%
“…For the remaining symbols, see • a parautochthonous Miocene fold (at the front of the Skole Nappe overthrust), thrust over the autochthonous deposits of the Carpathian Foredeep (the PW-3 well) with the thrust amplitude on the order of 1 km; • the subhorizontal autochthon, somewhat tectonically disturbed at depth (the PW-5 well), with basal lower Badenian deposits overlying (with a stratigraphic gap) the Upper Cretaceous marls (the ŁG-1 well). Krzywiec et al (2014) presented an alternative interpretation of the geological structure of the thrust front in the Pogórska Wola area (Fig. 1, cross section A), based on interpretation of a seismic 3D survey.…”
Section: Specific Features Of the Tectonics Of The Miocene Molassementioning
confidence: 99%